On the Slow Movement of Brahms's F-Minor Clarinet Sonata: Thirds-Cycles, Diatonie, and Todesangst - Edward Klorman (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2016)
The slow movement (Andante un poco adagio) of Brahms’s Sonata in F Minor for Piano and Clarinet, op. 120, no. 1, poses two significant challenges for a Schenkerian analysis: (1) pervasive, surface-level rhythmic displacements throughout the A section obscure the relationship between melody and bass; and (2) the B section is organized as a major-thirds cycle, a procedure that has often been regarded as incompatible with the underlying Diatonie of Schenker’s framework. This study develops two plausible interpretations of the ambiguous A section, of which one is selected for its clearer alignment of outer-voice counterpoint with formal function. The B section is analyzed as a ninth-progression, composed-out as a whole-tone scale. The chords of the major-thirds cycle are interpreted as consonant support for certain notes within that scale. In light of this movement’s ethereal quality (and of the nostalgia in much of Brahms’s late music), the juxtapositions of diatonic and chromatic spaces are interpreted in terms of Todesangst, since motives that require particular resolutions in diatonic contexts are relieved of such obligations when they recur in chromatic spaces.
Keywords: ambiguity; Brahms; clarinet; Diatonie; op. 120; rhythmic displacement; Schenkerian analysis; thirds-cycle; Todesangst